Deep sea floor observations of typhoon driven enhanced ocean turbulence. (May 2020) - Haren, Hans van; Chi, Wu-Cheng; Yang, Chu-Fang; Yang, Yiing-Jang; Jan, Sen
Highlights: Tropical cyclone recorded concurrently in geophysical and oceanographic instruments. Inertial temperature variations at 3000 m seafloor one day before arrival of cyclone. Inertial and tidal internal waves generate turbulence with >200 m overturns. Abstract: The impact of large atmospheric disturbances on deep benthic communities is not well known quantitatively. Observations are scarce but may reveal specific processes leading to turbulent disturbances. Here, we present high-resolution deep-ocean observations to study potential turbulent mixing by a large atmospheric disturbance. We deployed an array of 100-Hz sampling-rate geophysical broadband Ocean Bottom Seismometers (OBSs) on the seafloor. Within the footprint of this array we also deployed an oceanographic 0.5-Hz sampling-rate vertical temperature sensor string covering the water phase between 7 and 207 m above the seafloor at about 3000 m depth off eastern Taiwan between June 2017 and April 2018. In September 2017, all instruments recorded Category 4 cyclone Typhoon Talim's passage northeast of the array one day ahead of the cyclone's closest approach when the cyclone's eye was more than 1, 000 km away. For 10 days, a group of near-inertial motions appeared most clearly in temperature. The group contained the largest inertial amplitudes in the ten month time series, and which led to turbulence dissipation rates O(10 −7 m 2 s −3 ). The observation reflects the importance of barotropic response to a cyclone and the propagation of inertio-gravity waves in weak density stratification. In addition to internal tides, these waves drove turbulent overturns larger than 200 m that were concurrently recorded by OBSs. The turbulent signals were neither due to seismic activity nor to ocean-surface wave action. Cyclones can generate not only microseisms and earth hums, as well as turbulence in the water column, producing additional ground motions. Quantified turbulence processes may help constrain models on sediment resuspension and its effect on deep-sea benthic life.